Ions Transfer Behavior during water washing for LiNi0.815Co0.15Al0.035O2: Role of Excess Lithium. (September 2020) - Huang, X.; Duan, J.; He, J.; Shi, H.; Li, Y.; Zhang, Y.; Wang, D.; Dong, P.; Zhang, Y.
Abstract: Rapid moisture and carbon dioxide uptake in Ni-rich materials deteriorates their processing properties, thermal stability and electrochemical performance. Water washing is a widely used method to efficiently remove Li-based residues from these materials. In this paper, a detailed investigation of ion behavior during washing was carried out for LiNi0.815 Co0.15 Al0.035 O2 (NCA). Multiple characterizations including inductive coupled plasma atomic emission spectrometry (ICP-AES), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) depth profiles show that certain amount of Li + and Al 3+ are lost from the near-surface of NCA during washing process, which is one of the key issues that lead washed samples suffer from poor electrochemical performance and structural stability. The excess LiOH·H2 O ratio in mixing and high temperature sintering during NCA synthesis has a remarkable effect on the Al 3+ dissolution ratio, and the loss rate of Al 3+ is as high as 23.14% for lithium excess ratio up to 10 at.%. Characterization analyses of the electrochemical performance, structure, morphology and elemental chemical state of the samples demonstrate that the dissolution of Li + and Al 3+ from NCA deteriorates the cyclic performance, structural stability and thermal stability. Graphical abstract: Image 1 Highlights: Ion transfer behavior of NCA during water washing has been studied. Li + and Al 3+ dissolute during water washing. Li excess ratio affects Li + and Al 3+ solution ratio. The Li + and Al 3+ ions at the outer surface are eluted preferentially. Surface Li + and Al 3+ absence worsens cycle performance and thermal stability of NCA.